Effects of Lersivirine on Canine and Rodent Thyroid Function. (July 2014) - Houle, Christopher D.; Finch, Gregory L.; Mauthe, Robert J.; Potter, David M.; Walisser, Jacqueline A.; Gardner, Iain B.; DeWit, Robert H.
Lersivirine is a nonnucleoside reverse transcriptase inhibitor (NNRTI) being developed for the treatment of HIV-1 infection. Like other NNRTIs, lersivirine is a potent enzyme inducer in rodents capable of inducing a number of hepatic enzymes including those involved in its own metabolism. Preclinically lersivirine has been associated with hepatocellular hypertrophy and thyroid gland follicular cell hypertrophy in rats, mice, and dogs. In rodents, we show that development of thyroid hypertrophy is related to the classic mechanism, namely increased thyroxine (T4) clearance secondary to induction of uridine-diphosphoglucuronosyltransferase (UDPGT) in the liver and a resulting increase in thyroid-stimulating hormone. Similarly, lersivirine-exposed dogs exhibit a significant increase in hepatic UDPGT enzyme activity along with increased T4 clearance although clear effects on serum thyroid hormone levels were less apparent. These effects on thyroid hormonal clearance in the dog suggest that thyroid gland hypertrophy in this species is due to the same mechanism shown to occur in rodents although, as expected, dogs better adapt to these effects and therefore maintain relatively normal thyroid hormonal balance. It is also notable that the minimal thyroid follicular hypertrophy that occurs in dogs does not progress as is seen in rodents. As is the case with rodents, these adaptive changes in the dog are not considered indicative of a human health risk.